The Adapted Resistance Training with Instability Randomized Controlled Trial for Gait Automaticity. Issue 1 (21st September 2020) - Vieira‐Yano, Bianca; Martini, Douglas N.; Horak, Fay B.; de Lima‐Pardini, Andrea; Almeida, Filipe; Santana, Vagner P.; Lima, Daniel; Batista, Alana X.; Marquesini, Raquel; Lira, Jumes; Barbosa, Egberto R.; Corcos, Daniel M.; et al.
ABSTRACT: Background: Deficits in the cerebellar locomotor region (CLR) have been associated with loss of gait automaticity in individuals with freezing of gait in Parkinson's disease (freezers); however, exercise interventions that restore gait automaticity in freezers are lacking. We evaluated the effects of the adapted resistance training with instability ([ARTI] complex exercises) compared with traditional motor rehabilitation (without complex exercises) on gait automaticity and attentional set‐shifting. We also verified associations between gait automaticity change and CLR activation change previously published. Methods: Freezers were randomized either to the experimental group (ARTI, n = 17) or to the active control group (traditional motor rehabilitation, n = 15). Both training groups performed exercises 3 times a week for 12 weeks. Gait automaticity (dual‐task and dual‐task cost [DTC] on gait speed and stride length), single‐task gait speed and stride length, attentional set‐shifting (time between Trail Making Test parts B and A), and CLR activation during a functional magnetic resonance imaging protocol of simulated step initiation task were evaluated before and after interventions. Results: Both training groups improved gait parameters in single task ( P  < 0.05), but ARTI was more effective than traditional motor rehabilitation in improving DTC on gait speed, DTC on stride length, dual‐task stride length, and CLR activation ( P  < 0.05). Changes in CLR activation were associated with changes in DTC on stride length ( r = 0.68, P = 0.002) following ARTI. Only ARTI improved attentional set‐shifting at posttraining ( P  < 0.05). Conclusions: ARTI restores gait automaticity and improves attentional set‐shifting in freezers attributed to the usage of exercises with high motor complexity. © 2020 International Parkinson and Movement Disorder Society